2021
DOI: 10.9778/cmajo.20200209
|View full text |Cite
|
Sign up to set email alerts
|

Injury-related deaths in the Ontario provincial trauma system: a retrospective population-based cohort analysis

Abstract: I n most countries, including Canada, injury remains the leading cause of death in the first 4 decades of life and accounts for more productive years of life lost than any other disease process. 1,2 People with major trauma experience a 20% mortality rate, and many survivors are left with permanent disability, 3 mental health difficulties 4-6 and a heightened risk of suicide. 4 In the last several decades, many regions 7 including Ontario 8 have developed "trauma systems" to coordinate care for severely injure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Both result from road traffic crashes. This corroborates the findings of previous studies that reported road traffic crashes as the most common cause of trauma-related deaths recorded in the AEU [3,4,17,27,[30][31][32][33]. Overall, there were more traumatic surgical deaths than non-traumatic surgical deaths.…”
Section: Discussionsupporting
confidence: 91%
“…Both result from road traffic crashes. This corroborates the findings of previous studies that reported road traffic crashes as the most common cause of trauma-related deaths recorded in the AEU [3,4,17,27,[30][31][32][33]. Overall, there were more traumatic surgical deaths than non-traumatic surgical deaths.…”
Section: Discussionsupporting
confidence: 91%
“…For example, it has been reported in 2021 that most injury deaths in Ontario prevailed in locations out-ofhospital settings or were managed at non-trauma centres, leaving access to specialized injury care despite public health's efforts in developing effective "trauma systems." 46 Utilizing publicly available findings, dedicating resources to integrate health data 47 into hospital board decisional process could generate powerful insights to generate evidence-based managerial projections of clinical resources allocations. This is of significant importance considering emergency department visits have been outpacing population growth for years now.…”
Section: Utilize Geolocated Analyticsmentioning
confidence: 99%
“…Considering that exposure to war-factors would vary from region to region, and thereby generate geolocated differentials in clinical epidemiology, multinomial logistic model of diagnosis status were used to project statistically significant estimates of clinical morbidity variability across the Ukrainian landscape and to map out team response patterns and routes in accordance to the statistical projections. For example, it has been reported in 2021 that most injury deaths in Ontario prevailed in locations out-of-hospital settings or were managed at non-trauma centres, leaving access to specialized injury care despite public health’s efforts in developing effective “trauma systems.” 46 Utilizing publicly available findings, dedicating resources to integrate health data 47 into hospital board decisional process could generate powerful insights to generate evidence-based managerial projections of clinical resources allocations. This is of significant importance considering emergency department visits have been outpacing population growth for years now.…”
Section: Analysis: Lessons From Ukrainementioning
confidence: 99%
“…Trauma remains one of the leading causes of death in adults [ 1 , 2 ]. Nearly all deaths after trauma occur within the first 24 h, and uncontrolled bleeding is the most significant cause of preventable death in severe traumatic injuries [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%